Technological pedagogical and content knowledge of teachers and senior secondary student numeration performance - Gogo, Zalmon Ibaan; Jerry, Igie Osahon; Lechi, Goodluck Kindness (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
This research investigated how the Technological, Pedagogical, and Content Knowledge (TPACK) of Mathematics teachers affected the academic performance of senior secondary students in numeration. The study utilized an analytical survey research design and focused on a population consisting of 16 Senior Secondary School (SSS) three Mathematics teachers and 2975 SSS three students from all the public senior secondary schools in the Ahoada East L.G.A. of Rivers State. The sample of 16 SSS three Mathematics teachers and 353 students constituted the sample for this study. The study employed a census sampling method to select 16 Mathematics teachers from SSS three levels, while a simple random sampling technique was used to select the student sample. Data was collected using the Teachers TPACK Self-Assessment Questionnaire (T2PACK – SAQ) and Numeration Performance Test (NPT). The reliability coefficients obtained for T2PACK – SAQ and NPT were 0.71 and 0.76, respectively. The research was guided by four research questions and two hypotheses. The research questions were answered using mean and standard deviation, with a mean criterion of 2.50. The hypotheses were tested using an independent sample t-test at a significance level of 0.05. The findings revealed that TPACK has a positive impact on attitudes towards technology use in Mathematics education and enhances effective teaching and learning of Mathematics. Additionally, it was observed that Mathematics teachers possess a high level of TPACK, and students taught numeration by teachers with high TPACK achieved significantly better results compared to those taught by teachers with low TPACK. However, the gender difference was not significant. As a result of this research, one of the key recommendations is for teachers to incorporate the TPACK framework into their Mathematics instruction to enhance student achievement. Furthermore, it is suggested that the Nigerian Educational Research and Development Council (NERDC) consider integrating the TPACK framework into the secondary school Mathematics curriculum, recognizing its beneficial impact on Mathematics education.